2012
DOI: 10.1038/jhh.2012.34
|View full text |Cite
|
Sign up to set email alerts
|

The association of c-reactive protein with arterial compliance in asymptomatic young adults: the bogalusa heart study

Abstract: Atherogeneis is a chronic progressive syndrome caused by endothelial dysfunction, vascular inflammation, vessel wall remodeling and eventual vascular flow compromise. Emerging data suggest that arterial compliance inversely correlates with atherogenesis and cardiovascular (CV) events. However, information is scant on the association of chronic systemic inflammation with arterial elasticity in young asymptomatic adults. The association of hsC-reactive protein (CRP) and central-vascular compliance was studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous reports have shown a significant correlation between C reactive protein (CRP) levels and aortic inflammation (30). CRP, a valuable marker for diagnosing atherosclerotic diseases, is considered as an early cardiovascular risk factor as arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown a significant correlation between C reactive protein (CRP) levels and aortic inflammation (30). CRP, a valuable marker for diagnosing atherosclerotic diseases, is considered as an early cardiovascular risk factor as arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, delineation of more readily detectable biomarkers would definitely be desirable. To this effect, assays of hsCRP have unfortunately failed to deliver with sufficiently predictive precision, thereby reinforcing the need for development of more accurate predictive approaches of CVD risk in pediatric populations [12-14]. …”
Section: Cardiovascular Disease Risk In Children: Obesity and Obstrucmentioning
confidence: 99%
“…Inflammation largely contributes to endothelial dysfunction and reduces NO bioavailability in healthy people [ 44 ]. In vivo , AA have higher levels of inflammation, specifically CRP, than their CA peers in healthy [ 11 ] and diseased cohorts. AA diabetic patients with microalbuminuria, a population associated with higher levels of CRP, showed a blunted response to vasodilators due to decreased levels of NO production [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence has demonstrated that plasma CRP level is not only a prognostic biomarker of CVD but also has a direct effect on endothelial cells (ECs) by reducing endothelial NO synthase (eNOS) mRNA and protein expression necessary for NO production [ 4 , 8 10 ]. CRP has also been associated with endothelial dysfunction, exhibited as diminished large artery compliance in AA but not in CA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%